Fluorescent Silica Nanoparticles in the Detection and Control of the Growth of Pathogen - Kethirabalan Chitra; Gurusamy Annadurai (Journal of Nanotechnology)
In this present study the bioconjugated fluorescent silica nanoparticles give an efficient fluorescent-based immunoassay for the detection of pathogen. The synthesized silica nanoparticles were polydispersed and the size of the silica nanoparticles was in the range of 114–164 nm. The energy dispersive X-ray spectrophotometer showed the presence of silica at 1.8 kev and the selected area diffractometer showed amorphous nature of silica nanoparticles. The FTIR spectrum confirmed the attachment of dye and carboxyl group onto the silica nanoparticles surface. The fluorescent silica nanoparticles showed highly efficient fluorescence and the fluorescent emission of silica nanoparticles occurred at 536 nm. The SEM image showed the aggregation of nanoparticles and bacteria. The growth of the pathogenic E. coli was controlled using silica nanoparticles; therefore silica nanoparticles could be used in food packaging material, biomedical material, and so forth. This work provides a rapid, simple, and accurate method for the detection of pathogen using fluorescent-based immunoassay.